Impact of results-based financing on effective obstetric care coverage: evidence from a quasi-experimental study in Malawi - Stephan Brenner; Jacob Mazalale; Danielle Wilhelm; Robin C Nesbitt; Terhi J Lohela; Jobiba Chinkhumba; Julia Lohmann; Adamson S Muula; Manuela De Allegri (BMC, 2018)
Abstract Background Results-based financing (RBF) describes health system approaches addressing both service quality and use. Effective coverage is a metric measuring progress towards universal health coverage (UHC). Although considered a means towards achieving UHC in settings with weak health financing modalities, the impact of RBF on effective coverage has not been explicitly studied. Methods Malawi introduced the Results-Based Financing For Maternal and Neonatal Health (RBF4MNH) Initiative in 2013 to improve quality of maternal and newborn health services at emergency obstetric care facilities. Using a quasi-experimental design, we examined the impact of the RBF4MNH on both crude and effective coverage of pregnant women across four districts during the two years following implementation. Results There was no effect on crude coverage. With a larger proportion of women in intervention areas receiving more effective care over time, the overall net increase in effective coverage was 7.1%-points (p = 0.07). The strongest impact on effective coverage (31.0%-point increase, p = 0.02) occurred only at lower cut-off level (60% of maximum score) of obstetric care effectiveness. Design-specific and wider health system factors likely limited the program's potential to produce stronger effects. Conclusion The RBF4MNH improved effective coverage of pregnant women and seems to be a promising reform approach towards reaching UHC. Given the short study period, the full potential of the current RBF scheme has likely not yet been reached.